2012
DOI: 10.1007/s11051-011-0686-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and ion release of alloy nanoparticles

Abstract: It is well-known that nanoparticles could cause toxic effects in cells. Alloy nanoparticles with yet unknown health risk may be released from cardiovascular implants made of Nickel–Titanium or Cobalt–Chromium due to abrasion or production failure. We show the bio-response of human primary endothelial and smooth muscle cells exposed to different concentrations of metal and alloy nanoparticles. Nanoparticles having primary particle sizes in the range of 5–250 nm were generated using laser ablation in three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
350
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(368 citation statements)
references
References 44 publications
17
350
1
Order By: Relevance
“…23 Similar to that earlier study, the “inhalation exposure” and “deposited dose” were calculated. “Inhalation exposure” is the aerosol mass entering the human respiratory system during an exposure event.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Similar to that earlier study, the “inhalation exposure” and “deposited dose” were calculated. “Inhalation exposure” is the aerosol mass entering the human respiratory system during an exposure event.…”
Section: Methodsmentioning
confidence: 99%
“…23 Here, we report the results of a quantitative exposure assessment for selected consumer sprays, which are supposed to be used as antiseptics, cosmetics and personal care products. Ten spray products initially identified by Nazarenko et al .…”
Section: Introductionmentioning
confidence: 99%
“…Positively charged mesoporous silica nanoparticles with a zeta potential of + 34.4 mV had an onset of clearance into the intestinal tract in less than 30 min compared to over 3 days with −17.6 mV negatively charged particles. There have been several reports which have confirmed the urinary and fecal excretion of various formulations and sizes of silica particles [39,49,50]. Huang and co-workers investigated the biodistribution of different silica nanoparticles with varying aspect ratios using ICP–OES and demonstrated that even larger silica nanoparticles could be excreted [51].…”
Section: Biodistribution and Toxicologymentioning
confidence: 99%
“…The availability of any desired Ag/Au ratio in a solid alloy, in combination with its ablation in liquid by lasers, gives access to colloidal alloy nanoparticles with defined compositions [35,36]. Since it has been recently shown that gold-silver nanoparticle surface patterns designed from co-sputtering of gold with silver showed a silver ion release disproportional to the silver content in the alloy, the question arises whether this effect will also be observed in the bioresponse to nanoparticles [37,38].…”
Section: Introductionmentioning
confidence: 99%